The Role of Interdisciplinary Collaboration in Cultivating Innovative Talents: Evidence from Sino-Foreign Cooperative Education - Mo, Fan (Journal of Educational Research and Policies, 2025)
Sino-foreign cooperative education, a key driver of higher education internationalization, is an important platform for cultivating top innovative talents. This study investigates the influence of interdisciplinary collaboration on talent development within these programs through an online survey of 740 faculty members and students from domestic and international universities involved in Sino-foreign cooperative education. The results demonstrate that interdisciplinary collaboration significantly enhances team innovation efficacy, which, in turn, stimulates individual innovative thinking. Specifically, higher levels of interdisciplinary collaboration strengthen team innovation efficacy, thereby fostering more dynamic, open, and flexible individual innovative thinking. Moreover, the positive effect of interdisciplinary collaboration on individual innovative thinking is contingent on the level of team innovation efficacy: it weakens when Team Innovation Efficacy is low, and strengthens when it is high. This study advances the theoretical understanding of innovative talent cultivation in Sino-foreign cooperative education and provides practical insights for optimizing program design to support high-level talent development.